Long term survival in primary pulmonary hypertension. Issue 7 (14th June 2004) - Halank, M; Marx, C; Hoeffken, G
Abstract : The mean survival of patients with severe primary pulmonary hypertension (PPH) is < 3 years without appropriate treatment. There are no long term reports on the spontaneous course of mild PPH over a longer period. Stable long term follow up is described of a 39 year old patient with PPH without treatment over a 30 year period. PPH had been diagnosed 30 years previously after right heart catheterisation (mean pulmonary artery pressure 35 mm Hg) and 30 years later, repeated measurements showed nearly unchanged haemodynamic parameters. Further examinations confirmed the diagnosis of PPH. It is suggested that PPH with modestly limited physical activity (New York Heart Association functional class II) does not always seem to coincide with progression of the disease and, therefore, it may be feasible to withhold treatment while closely monitoring these patients.